A comprehensive guide to managing astigmatism in the cataract patient. (December 2014) - Coleman, Michael J; Stark, Walter J; Daoud, Yassine J
<x xml:space="preserve">Abstract</x> Improvements in cataract surgery and ophthalmic lens technology have turned cataract surgery into a refractive procedure. Patients are expecting that they will no longer require contact lens or glasses for excellent vision. In order to meet the patient's expectations, the surgeon must be meticulous with preoperative measurements and precise with the intraoperative alignment of the implanted toric lens. Technological advances in intraoperative aberrometry and image guidance software will improve intraoperative alignment of astigmatism correcting lens. Despite the improvements in measurements, unforeseen refractive outcomes will occur and it is critical that the cataract surgeon is equipped to correct any problems. A systematic evaluation should be undertaken to find the source of the error. Complete ocular exam with lens axis measurement, manifest refraction and repeat corneal measurements should be done. Treatment options to correct residual refractive error include toric lens rotation, laser vision correction with photorefractive keratectomy or laser in-situ keratomileusis, piggyback lens placement or intraocular lens (IOL) exchange. Prior to selecting a treatment option, it is important to compare pre- and post-operative calculations. If preoperative calculations are correct, a vector analysis can be performed to determine suggested IOL adjustment to correct the refractive error. If toric lens rotation does not provide a satisfactory refractive outcome, laser vision correction is recommended as a first option. If the patient is not a good refractive candidate, an IOL exchange with a monofocal lens or with the appropriate toric lens, if the loops can be safely placed in the bag, is advocated.